Doing good with other people's money: A charitable giving experiment with students in environmental sciences and economics - Frederik Carlsson; Mitesh Kataria; Elina Lampi; M. Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We augment a standard dictator game to investigate how preferences for an environmental project relate to willingness to limit others' choices. We explore this issue by distinguishing three student groups: economists, environmental economists, and environmental social scientists. We find that people are generally disposed to grant freedom of choice, but only within certain limits. In addition, our results are in line with the widely held belief that economists are more selfish than other people. Yet, against the notion of consumer sovereignty, conomists are not less likely to restrict others' choices and impose restrictions closer to their own preferences than the other student groups.
Keywords: C92; D64; 330; dictator game; charitable giving; social preferences; paternalism; Altruismus; Spende; Soziale Wohlfahrtsfunktion; Wildtierschutz; Test; Schweden